Legal Regulation of Commercial Intermediary Agreements under the EU Law - M. A. Anosov (Московский журнал международного права, 2010)
The article considers development of intermediary contracts under EU law. The author considers effective EU supranational legislation as well as “soft law” instruments regarding representation, franchise agreements, distributorship agreements and commercial agency agreement.